KARAKTERISTIK MUTU DODOL KETAN DENGAN PENAMBAHAN PISANG AMBON DAN JAMBU BIJI - Manogar, Borsak; Pato, Usman; Ayu, Dewi Fortuna (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was to determine and obtain the optimal ratio of glutinous rice flour, ambon banana, and guava for making glutinous dodol. The reseach used a Completely Randomized Design (CRD) experiment with 5 treatments and 3 replications. The treatments were the ratio of glutinous rice flour, ambon banana, and guava porridge (100% : 0% : 0%, 40% : 54% : 6%, 40% : 48% : 12%, 40% : 42% : 18%, and 40% : 36% : 24%). Data were statistically analyzed using Analysis of Variance (ANOVA) and followed by Duncan’s New Multiple Range Test (DNMRT) test at 5% level. Results of the study show that the ratio of glutinous rice flour, ambon banana, and guava porridge significantly affected the moisture, fat, protein, sucrose, and crude fiber contents, with hedonic and descriptive sensory test, such as color, aroma, texture, and taste. The best treatment was the ratio of glutinous rice flour, ambon banana, and guava porridge (40% : 48% : 12%) which had moisture, fat, protein, sucroce, and crude fiber of 16,39%, 3,03%, 2,40%, 47,71%, and 7,05% respectively. The result of the descriptive test of the glutinous dodol from the best treatment was a brownish, a scented of banana, chewy texture, and feels of banana, while hedonic test was preferred by panelist. Keywords: Glutinous dodol, glutinous rice flour, ambon banana, guava